Development of the Fun School Movement Program in Elementary Schools in Support of the Merdeka Belajar Curriculum - Firdaus, Fery Muhamad; Prasojo, Lantip Diat; Wijaya, Widia Murni; Fadhli, Rahmat; Aman, Aman; Rochmah, Evy Nur; Raharjo, Amrih Setyo (International Journal of Public Devotion, 2024)
The Fun School Movement Program (GSM) is a program that encourages a positive, fun, safe learning environment and evokes student enthusiasm for learning. This program aims to improve the quality of learning and good character of students. In addition, the emergence of the concept of freedom of learning for students and teachers through the independent learning curriculum makes the problems faced by schools more complex. This activity aims to assist schools in developing the GSM program and increasing understanding of the independent learning curriculum. The activity was carried out six times which included discussion, practice and program assistance in Depok District, Sleman Regency, Special Region of Yogyakarta. The results of the training and mentoring activities show that there has been an increase in the understanding of educators on the concept of GSM and the Independent Learning Curriculum. In addition, teachers are also able to design products in the form of GSM programs that can be implemented in their schools